HS–GC–MS–O analysis and sensory acceptance of passion fruit during maturation - Janzantti, Natália S. [UNESP]; Monteiro, Magali [UNESP] (Springer Nature, 2017)
The odor-active compounds of the conventional yellow passion fruit influence the aroma during ripeness and the acceptance of the juice. HS–GC–MS and GC–OSME analysis and sensory acceptance of the conventional passion fruit from different stages of ripeness were studied to characterize the aroma of the fruit and, aroma and flavor of the juice. Ethyl butanoate, ethyl hexanoate and propyl acetate showed high odoriferous importance in the passion fruit from the 1/3 yellow skin color. Cis-3-hexen-1-ol and diethyl carbonate plus the odor-active compounds from the 1/3 yellow skin color showed high odoriferous importance in the 2/3 yellow skin color, and butyl acetate and alpha-terpineol plus the same odor-active compounds from 2/3 were the most important for the 3/3 yellow skin color. There was difference in the aroma and flavor of the juices, with higher acceptance means for the passion fruit from the 3/3 yellow skin color. The passion fruit volatile compounds peak area, odoriferous intensity and sensory acceptance of the juices increased during ripeness, indicating that the conventional passion fruit characteristic aroma is completely expressed when the fruit reaches the whole maturation, at the 3/3 yellow skin color.
Keywords: HS–GC–MS–OSME; Olfactometry; Passion fruit (Passiflora edulis Sims f. flavicarpa Deg.); Sensory acceptance; Stage of ripeness